Nonmotor symptoms in primary adult‐onset cervical dystonia and blepharospasm. Issue 2 (18th December 2016) - Yang, Jing; Shao, Na; Song, Wei; Wei, Qianqian; Ou, Ruwei; Wu, Ying; Shang, Hui‐Fang
Abstract: Background: The nature and frequency of nonmotor symptoms in primary adult‐onset cervical dystonia (CD) and blepharospasm (BSP) patients in Chinese populations remain unknown. Methods: Hamilton's Depression Scale (HAMD), Hamilton's Anxiety Scale (HAMA), Addenbrooke's Cognitive Examination Revised (ACE‐R), Pittsburgh Sleep Quality Index and Epworth Sleepiness Scale were used to evaluate NMS in 120 patients with primary focal adult‐onset dystonia (60 with BSP and 60 with CD) and 60 age‐, sex‐, and education level‐ matched healthy controls (HCs). Motor symptoms of BSP and CD patients were evaluated by Jankovic rating scale and Toronto Western Spasmodic Torticollis Rating Scale‐severity scale separately. Results: Twenty patients had depression, and 29 patients had anxiety. The mean HAMD and HAMA scores were significantly higher in patient groups. Thirty‐six patients had cognitive decline based on the cut‐off score of 75. The total score and scores of each domain of ACE‐R were significantly lower in patient groups than that in HCs. Quality of sleep was impaired in patient groups, and patients with CD had worse quality of sleep than patients with BSP. Thirty‐three BSP patients and 43 CD patients suffered from sleep disorder separately. The frequency of excessive daytime sleepiness did not differ between patients and HCs. No significant correlation was found between NMS and motor severity in the two forms of dystonia. Conclusions: Current study suggests that NMS are prevalent in Chinese CD and BSP patients, and the motor severity of dystonia did not contribute to the severity of nonmotor symptoms. Assessment of nonmotor symptoms should be considered in clinical management of focal dystonia Abstract : Patients with dystonia may develop several nonmotor symptoms (NMS). NMS were evaluated in 120 patients with cervical dystonia and blepharospasm. We found depression, anxiety, sleep disorder and cognitive decline are common in these patients, and the severity of motor symptom did not contribute to the severity of NMS in craniocervical dystonia.